We are not educating the future clinical health professional workforce adequately for e-health competence: Findings of an Australian study - Dattakumar, A.; Gray, K.; Butler-Henderson, Kerryn; Maeder, A.; Chenery, H. (IOS Press BV, 2012)
This paper reports on a national study of the present approaches in Australian tertiary education, to preparing future clinical health professionals to work competently in an increasingly e-health enabled healthcare sector. The argument for increasing clinical health professionals' knowledge about e-health and health informatics has been advanced repeatedly over past decades in Australia and elsewhere. However, peer-reviewed accounts of good practice in implementing and evaluating e-health education in health profession degrees anywhere are scarce. Our study reports on surveying approximately 100 degree coordinators in 40 clinical health professions in 30 universities across Australia. It finds that currently, teaching and assessment of future clinical health professionals does not ensure that Australia will have a clinical workforce that is adequately professionally empowered to work with e-health. This paper provides important baseline data for planning improvements to e-health education for Australia's future clinical health professionals.